Método líquen: uma proposta para auxiliar o ensino de aritmética nos anos iniciais - Zancan, Sabrina (2017)
Analyzing didactic activities proposed by teachers to first year students of elementary school, we note that they address numerical sequence, count, addition and subtraction operations, but we did not find a systematized teaching of mathematical contents with the aim of developing the knowledge necessary for mental calculation. In spite of this, some students develop autonomous abilities with this type of calculation, while others remain dependent on counting, causing a disparity in the classroom. One of the consequences of that disparity is anxiety related to the learning of Mathematics by those who do not use mental calculation, starting from the first years of schooling, causing possible deficiencies in the mathematical formation of these students. However, the activities analyzed have a potential that is not harnessed. We realized that it is possible to systematize these activities to allow a better understanding of the numerical properties and promote the development of mental calculation strategies by students. Through the systematization of some activities, linked to actions that facilitate learning, we developed the Liquen Method, whose objectives are: assist students in the construction of the necessary knowledge of mental calculation strategies and to promote class leveling in relation to the improvement of their basic arithmetic calculation skills in agility and accuracy. The Lichen Method has a set of specific actions of daily work and a set of tasks with low cost, carried out by the whole class, but individually by the students, in the classroom. The method assists in the construction of number sense and numeric operations and properties, inserting the knowledge and, thus, stimulating the use of calculation strategies for numbers smaller than 20, in a systematic, simple and differentiated way, since the first year of elementary school, starting at a point of dominance of all students and gradually evolving, so that everyone develops the greatest potential of their abilities. We implemented the Liquen Method for four years in seven schools. The method was used by 34 different teachers and approximately 700 students from first to fifth grade classes for at least one school year. Assessment by means of tests showed that students who used the Lichen Method were more agile and with greater accuracy compared to basic arithmetic and the classes became more uniform in these questions: agility and accuracy for basic arithmetic. Evaluations of calculation strategies, used in the answers to addition questions contained in a deck, showed that more than 50% of students are using mental calculation strategies in simple additions of numbers smaller than 20, in the third and fourth year classes, who used the method for two or three school years. While the percentage is less than 20% in classes of the same year that did not use the method. Those investigations have shown that the Lichen Method, with its tasks and actions, promotes the development of mental calculation.